Comparing Public and Private School Students' Academic Performance (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Thesis explores the distinct approaches to education and learning strategies employed in government versus private schools within the Sagar Division, Madhya Pradesh. The study aims to evaluate how these differing educational tactics impact student academic performance, with a particular focus on identifying any significant variations between the two types of institutions. Additionally, the research delves into the influence of gender on learning outcomes and the role of teacher training in shaping these results.